Verification of cutaneous leishmaniasis - D. V. Zaslavsky; YE. M. Andriyenko; I. Y. Aleksandrova; YE. L. Matveyeva; S. YE. Semyonova; M. E. Zuyev; A. A. Gaiduk (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article presents a case study of cutaneous leishmaniasis in a child. The patient stayed for several months in a leishmaniasis endemic area - in Tajikistan. This case is interesting from the point of view of verification of the infection that is not endemic in Russia.